PENGARUH FLYPAPER EFFECT PADA DANA KEISTIMEWAAN DAN PENDAPATAN ASLI DAERAH TERHADAP PERTUMBUHAN EKONOMI PROVINSI DAERAH ISTIMEWA YOGYAKARTA - Winaya Miranda Eka Puteri; Maunty Isnaeny; Fadjar Tri Sakti (Universitas Muhammadiyah Sumatera Utara, 2025)
This study examines how the Special Autonomy Fund (Danais) and Regional Own-Source Revenue (PAD) contribute to the dynamics of economic growth in the Special Region of Yogyakarta (DIY) during the period 2021–2024, using a quantitative descriptive–causality approach. The findings indicate that although Danais, PAD, and GRDP all show year-to-year increases, their patterns of change do not demonstrate a direct relationship that explains the influence of Danais or PAD on economic growth. A flypaper effect may occur when regional economic activity is more strongly influenced by central government transfers than by the region’s own revenue capacity. Further investigation is needed to understand how reliance on Danais shapes spending priorities and economic development in DIY.Keywords:Economic Growth , Special Autonomy Fund, Own Source Revenue